Long-acting anti-freezing cooling liquid with ultralow conductivity and preparation method thereof

By using ultra-low conductivity long-term antifreeze coolant in the cooling system of new energy electric vehicle, the safety hazards and material compatibility problems of traditional coolant for electric vehicles are solved, and the effects of low conductivity, good thermal conductivity and long-term protection are achieved.

CN119684980APending Publication Date: 2025-03-25GUANGZHOU BIAOBANG CAR CARE IND
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510045622.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-13
Publication Date
2025-03-25

AI Technical Summary

Technical Problem

The cooling system of new energy electric vehicles poses safety risks to traditional coolants with high conductivity, and traditional coolants cannot meet the chemical compatibility and thermal conductivity efficiency requirements of new materials used in electric vehicles.

Method used

Develop a long-term antifreeze coolant with ultra-low conductivity, using components such as copper corrosion inhibitors, aluminum corrosion inhibitors and modifiers to achieve low conductivity, good thermal conductivity and long-term protection by forming a stable protective film and efficient thermal conductivity network.

Benefits of technology

It significantly reduces the conductivity of the coolant, reduces the risk of battery fire, improves chemical compatibility and heat conduction efficiency, and extends the service life of the cooling system.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005238307240000071
    Figure BDA0005238307240000071
  • Figure BDA0005238307240000091
    Figure BDA0005238307240000091
  • Figure BDA0005238307240000101
    Figure BDA0005238307240000101
Patent Text Reader

Abstract

The invention relates to the field of cooling liquid for new energy automobiles, in particular to long-acting anti-freezing cooling liquid with ultralow conductivity and a preparation method of the long-acting anti-freezing cooling liquid. The invention relates to a long-acting anti-freezing cooling liquid with ultralow conductivity. The long-acting anti-freezing cooling liquid comprises a copper corrosion inhibitor, an aluminum corrosion inhibitor, a pH value regulator, a defoaming agent, ethylene glycol, deionized water and a modifier, the modifier is prepared from coconut shells and nanometer aluminum oxide, and the modifier is obtained after the coconut shells are carbonized and loaded with the nanometer aluminum oxide. The cooling liquid disclosed by the invention has ultralow conductivity, so that the risk of battery fire caused by leakage is effectively reduced; the coating has good chemical compatibility and can be perfectly compatible with various materials in the cooling system of the electric automobile, so that corrosion and damage are reduced; and excellent heat conduction efficiency is achieved, efficient and stable operation of the cooling system can be guaranteed, and the service life of the electric automobile is prolonged.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of coolant for new energy vehicles, and more specifically, to a long-lasting antifreeze coolant with ultra-low conductivity and a preparation method thereof. Background Art

[0002] With the transformation and upgrading of the global automotive industry, new energy electric vehicles are gradually becoming the mainstream of the market. However, compared with fuel vehicles, new energy electric vehicles have significant differences in the design and material application of the cooling system. The coolant products widely sold on the market are mainly designed for fuel vehicles. Most of them use inorganic salt formulas or organic acid / inorganic salt mixed formulas with high conductivity. This characteristic may not be a problem in the cooling system of fuel vehicles, but it may bring serious safety hazards in new energy electric vehicles. The battery pack of electric vehicles has extremely high requirements for electrical insulation performance. Once the high-conductivity coolant leaks, it will greatly increase the risk of battery fire or short circuit, seriously threatening the safety of the vehicle and passengers.

[0003] In addition, the materials used in the cooling system of electric vehicles are also different from those of fuel vehicles. Electric vehicles use a large number of new materials such as aluminum alloys, copper alloys, high-performance plastics and composite materials, which have more stringent requirements on the chemical compatibility, corrosion resistance and thermal conductivity of coolants. Traditional fuel vehicle coolants can no longer fully meet these special requirements. Therefore, it is urgent to develop a new coolant product that is tailored to the characteristics of electric vehicles. Summary of the invention

[0004] In order to solve the above problems, the present application provides an ultra-low conductivity long-lasting antifreeze coolant and a preparation method thereof.

[0005] In a first aspect, the present application provides a long-term antifreeze coolant with ultra-low conductivity, which adopts the following technical scheme: an ultra-low conductivity long-term antifreeze coolant, comprising the following components in terms of mass percentage: 0.1-0.2% copper corrosion inhibitor, 0.15-0.22% aluminum corrosion inhibitor, 0.18-0.25% pH value regulator, 0.01-0.05% defoamer, ethylene glycol, 35-45% deionized water, and 0.01-0.05% modifier; The modifier is prepared by carbonizing coconut shell and loading nano-alumina.

[0006] Preferably, the copper corrosion inhibitor comprises a mixture of one or more of benzotriazole, tolutriazole, and sodium mercaptobenzothiazole.

[0007] Preferably, the aluminum corrosion inhibitor includes a mixture of one or more of sodium silicate and phenyl silicate.

[0008] Preferably, the particle size of the nano-alumina is 10-30 nm.

[0009] Preferably, the pH adjuster is triethanolamine.

[0010] Preferably, the defoamer is a silicone defoamer.

[0011] Preferably, the deionized water is ultrapure water prepared by multi-stage RO reverse osmosis with EDI filtration equipment, with a conductivity of <1μs / cm; Ethylene glycol is polyester-grade ethylene glycol extracted from petroleum refining, with a purity of 99.99% and an electrical conductivity of <0.1μs / cm. It is odorless, transparent, free of impurities, will not clog the pipeline system, and will not cause leakage hazards.

[0012] The coolant provided in the present application uses a variety of corrosion inhibitors in combination, fully utilizing the advantages of each type of corrosion inhibitor to produce a comprehensive effect, which can not only provide better protection for metals, but also extend durability and maintain long-term protection.

[0013] In the process of metal corrosion, whether it is chemical corrosion or electrochemical corrosion, the valence state of the metal increases while the valence state of an element in a certain substance in the medium decreases, which is an oxidation-reduction reaction. The key technical point of antifreeze products is how to avoid and prevent the ionization reaction of metal materials.

[0014] The existing anti-corrosion mechanism of organic carboxylic acid antifreeze is to use the adsorption of carboxylic acid on the metal surface to form a film, which plays an isolation and protection role. However, once the components, pH value and other parameters of the antifreeze change, desorption reaction is likely to occur, causing corrosion of metal parts.

[0015] The present application uses copper corrosion inhibitors and aluminum corrosion inhibitors to form a stable and strong protective film on the interface between metal and antifreeze to mask metal ions, and cooperate and dissolve with the remaining components to construct a weakly alkaline, low-conductivity, non-ionic coolant environment. While efficiently dissipating heat and preventing freezing at low temperatures, it protects the metal parts and sealing parts of the cooling system to the greatest extent, achieving the effect of one-time addition and ultra-long-term use.

[0016] The antifreeze coolant product provided by the present application has stable quality, extremely low electrical conductivity, and excellent anti-corrosion, anti-freeze and anti-boiling properties.

[0017] Not only that, the introduction of the modifier further reduces the electrical conductivity of the coolant and improves its thermal conductivity. Specifically, nano-alumina itself has good thermal conductivity. When loaded inside the carbonized coconut shell, the modifier formed can build an efficient thermal conductivity network. The rich pore structure contained in the carbonized coconut shell provides an ideal attachment site for nano-alumina, and also promotes rapid heat transfer by increasing the heat exchange area. The biochar structure formed by the combination of nano-alumina and coconut shell is used in the freezing liquid, which can significantly improve its thermal conductivity efficiency.

[0018] At the same time, the insulating properties of coconut shell itself are retained during the modification process, which is crucial for reducing the conductivity of the refrigerant. The uniform dispersion of nano-alumina in the carbonized coconut shell effectively avoids the formation of conductive pathways, thus ensuring the low conductivity of the refrigerant.

[0019] The synergistic effect of the modifier not only balances the thermal and electrical conductivity, but also improves the stability and corrosion resistance of the refrigerant. The modifier loaded with nano-alumina can have good dispersibility and stability in the refrigerant, preventing the agglomeration and sedimentation of particles, thereby extending the service life of the refrigerant. At the same time, they jointly form a protective film on the surface of the refrigerant, effectively preventing the chemical reaction between the refrigerant and metal parts, and protecting the integrity of the automobile cooling system.

[0020] In summary, the coolant of the present application has ultra-low electrical conductivity, which effectively reduces the risk of battery fire caused by leakage; it has good chemical compatibility and can be perfectly compatible with various materials in the cooling system of electric vehicles, reducing corrosion and damage; it also has excellent thermal conduction efficiency, which can ensure the efficient and stable operation of the cooling system and extend the service life of electric vehicles.

[0021] In a second aspect, the present application provides a method for preparing a long-lasting antifreeze coolant with ultra-low conductivity, using the following technical solution: A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity comprises the following steps: Step 1: preparing a modifier, comprising the following steps: Step 1a: chopping coconut shells to obtain coconut shell powder; Step 1b: mixing coconut shell powder with deionized water, and subjecting the mixture to microwave treatment at 300-400 W for 10-20 min to obtain a microwave-treated product; Step 1c: heating the microwave-treated product at 200-250° C. for 2-4 h to obtain a heated reaction product; Step 1d: filtering, drying and heating the reactants to obtain a product to be treated; Step 1e: uniformly mixing the object to be treated with nano-alumina, and then calcining at 650-750° C. for 4-6 hours to obtain a modifier; The mass ratio of the object to be treated to the nano-alumina is 1:(0.3-0.6), based on the mass of the object to be treated; Step 2: Mix ethylene glycol and deionized water until uniform; Step 3: Add the pH adjuster to the material in step 2 and mix well; Step 4: Cool the material in step 3 to below 50° C., add copper corrosion inhibitor and aluminum corrosion inhibitor, and stir until completely dissolved; Step 5: Add the remaining raw materials to the material in step 4, mix until uniform, and obtain a long-lasting antifreeze coolant with ultra-low conductivity.

[0022] By adopting the above technical solution, the coconut shell is treated by microwave and heating to change its internal structure, so that a specific biochar structure loaded with nano-alumina is formed during subsequent calcination, so that the modifier has better thermal conductivity and lower electrical conductivity in the coolant.

[0023] Preferably, in step 1b, the mass ratio of coconut shell powder to deionized water is 1:(3-6), based on the mass of coconut shell powder.

[0024] Preferably, the particle size of the coconut shell powder is 0.1-0.3 mm.

[0025] By adopting the above technical solution, the particle size of coconut shell powder and the mass ratio of coconut shell powder to deionized water are further limited, providing better basic conditions for subsequent combination with nano-alumina.

[0026] Preferably, after the remaining raw materials are added in step 5, stirring is carried out at a rotation speed of 800-1000 r / min.

[0027] In summary, this application has the following beneficial effects: 1. The coolant of the present application fully utilizes the unique advantages of the components through the synergistic effect of copper corrosion inhibitor, aluminum corrosion inhibitor and modifier, so that the coolant has ultra-low conductivity, which can not only provide excellent protection for metals, but also significantly enhance durability and ensure long-term protection effectiveness, aiming to achieve comprehensive protection of metal materials, extend service life, and meet the needs of efficient and long-lasting cooling.

[0028] 2. In this application, methylbenzotriazole, phenyl silicate, etc. are preferably used to form a stable protective film at the interface between the metal and the antifreeze liquid, and at the same time, a weakly alkaline, low-conductivity, non-ionic coolant environment is constructed to achieve efficient heat dissipation, low-temperature antifreeze, and long-term protection of the cooling system metal and sealing components.

[0029] 3. This application significantly improves the thermal conductivity of the coolant and further reduces the electrical conductivity through a specially prepared modifier. Nano-alumina is loaded inside the carbonized coconut shell, and uses its good thermal conductivity and the rich pore structure of the carbonized coconut shell to build an efficient thermal conductive network, increase the heat exchange area, and significantly improve the thermal conductivity. At the same time, the insulating properties of the coconut shell are retained during the modification process, and the uniform dispersion of nano-alumina avoids the formation of a conductive path, ensuring the low conductivity of the coolant. DETAILED DESCRIPTION

[0030] The present application is further described in detail below in conjunction with embodiments.

[0031] The raw materials used in the following examples and comparative examples are all commercially available products. Example

[0032] Example 1 The invention discloses an ultra-low conductivity long-acting antifreeze coolant, comprising the following components: a copper corrosion inhibitor, an aluminum corrosion inhibitor, a pH value regulator, a defoaming agent, ethylene glycol, deionized water and a modifier.

[0033] The specific content of each component is shown in Table 1.

[0034] The copper corrosion inhibitor was methylbenzotriazole, which was purchased from Nanjing Shengbai International.

[0035] The aluminum corrosion inhibitor was phenyl silicate, which was purchased from Hebei Jingmai Technology Co., Ltd.

[0036] The pH adjuster is triethanolamine.

[0037] The defoaming agent is an organosilicon defoaming agent, model: AD-46.

[0038] Deionized water is ultrapure water prepared by multi-stage RO reverse osmosis with EDI filtration equipment, with a conductivity of <1μs / cm.

[0039] Ethylene glycol is polyester-grade ethylene glycol extracted from petroleum refining, with a purity of 99.99% and a conductivity of <0.1μs / cm.

[0040] This embodiment also provides a method for preparing an ultra-low conductivity long-acting antifreeze coolant, comprising the following steps: Step 1: preparing a modifier, comprising the following steps: Step 1a: Wash the coconut shell with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the coconut shell into particles with a diameter of 0.1-0.3 mm to obtain coconut shell powder.

[0041] Step 1b: Mix coconut shell powder with deionized water in a ratio of 1:5.

[0042] Then, the mixture was treated with microwaves at 350 W for 15 min to obtain a microwave-treated product.

[0043] Step 1c: Heat the microwave-treated product at 230° C. for 3 h to obtain a heated reaction product.

[0044] Step 1d: Filter the heated reactants, and dry the solid portion using hot air to a constant weight to obtain a product to be treated.

[0045] Step 1e: Mix the object to be treated with nano-alumina (nano-alumina particle size is 20nm) at a mass ratio of 1:0.5 and place in a tube furnace. Heat to 700°C at a heating rate of 10°C / min, react for 5h in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it under hot air at 60°C to constant weight to obtain a modifier.

[0046] Step 2: Add ethylene glycol and deionized water into a reaction kettle and stir at a speed of 650 r / min to completely mix them to obtain a solvent.

[0047] Step 3: Slowly add the pH adjuster into the reactor (the addition rate is controlled to be completed within 1 hour) and observe the temperature.

[0048] Step 4: Keep the material temperature of step 3 at 50°C. After the material is completely dissolved, slowly add the copper corrosion inhibitor and the aluminum corrosion inhibitor and stir until it is completely dissolved.

[0049] Step 5: Add the remaining raw materials to the material in step 4, stir at a speed of 900 r / min for 10 minutes to obtain a long-lasting antifreeze coolant with ultra-low conductivity.

[0050] Example 2 An ultra-low conductivity long-lasting antifreeze coolant, which is different from Example 1 in that: The copper corrosion inhibitor is benzotriazole.

[0051] The aluminum corrosion inhibitor is sodium silicate.

[0052] The specific content of each component is different, see Table 1 for details.

[0053] A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity is different from that of Example 1 in that some parameters are different. Specifically, the method comprises the following steps: Step 1: preparing a modifier, comprising the following steps: Step 1a: Wash the coconut shell with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the coconut shell into particles with a diameter of 0.1-0.3 mm to obtain coconut shell powder.

[0054] Step 1b: Mix coconut shell powder and deionized water in a ratio of 1:3.

[0055] Then, the mixture was treated with microwave at 300 W for 20 min to obtain a microwave-treated product.

[0056] Step 1c: Heat the microwave-treated product at 200° C. for 4 h to obtain a heated reaction product.

[0057] Step 1d: Filter the heated reactants, and dry the solid portion using hot air to a constant weight to obtain a product to be treated.

[0058] Step 1e: Mix the object to be treated with nano-alumina (nano-alumina particle size is 10 nm) at a mass ratio of 1:0.3 and place in a tube furnace. Heat to 650°C at a heating rate of 10°C / min, react for 6 hours in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it to constant weight under 60°C hot air to obtain a modifier.

[0059] Step 2: Add ethylene glycol and deionized water into a reaction kettle and stir at a speed of 500 r / min to completely mix them to obtain a solvent.

[0060] Step 3: Slowly add the pH adjuster into the reactor (the addition rate is controlled to be completed within 1 hour) and observe the temperature.

[0061] Step 4: Keep the material temperature of step 3 at 50°C. After the material is completely dissolved, slowly add the copper corrosion inhibitor and the aluminum corrosion inhibitor and stir until it is completely dissolved.

[0062] Step 5: Add the remaining raw materials to the material in step 4, stir at a speed of 800 r / min for 15 minutes, and obtain a long-lasting antifreeze coolant with ultra-low conductivity.

[0063] Example 3 An ultra-low conductivity long-lasting antifreeze coolant, which is different from Example 1 in that: The specific content of each component is different, see Table 1 for details.

[0064] A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity is different from that of Example 1 in that some parameters are different. Specifically, the method comprises the following steps: Step 1: preparing a modifier, comprising the following steps: Step 1a: Wash the coconut shell with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the coconut shell into particles with a diameter of 0.1-0.3 mm to obtain coconut shell powder.

[0065] Step 1b: Mix coconut shell powder and deionized water in a ratio of 1:6.

[0066] Then, the mixture was treated with microwave at 400 W for 10 min to obtain a microwave-treated product.

[0067] Step 1c: Heat the microwave-treated product at 250° C. for 2 h to obtain a heated reaction product.

[0068] Step 1d: Filter the heated reactants, and dry the solid portion using hot air to a constant weight to obtain a product to be treated.

[0069] Step 1e: Mix the object to be treated with nano-alumina (nano-alumina particle size is 30nm) at a mass ratio of 1:0.6 and place in a tube furnace. Heat to 750°C at a heating rate of 10°C / min, react for 4 hours in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it under hot air at 60°C to constant weight to obtain a modifier.

[0070] Step 2: Add ethylene glycol and deionized water into a reaction kettle and stir at a speed of 800 r / min to completely mix them to obtain a solvent.

[0071] Step 3: Slowly add the pH adjuster into the reactor (the addition rate is controlled to be completed within 1 hour) and observe the temperature.

[0072] Step 4: Keep the material temperature of step 3 at 50°C. After the material is completely dissolved, slowly add the copper corrosion inhibitor and the aluminum corrosion inhibitor and stir until it is completely dissolved.

[0073] Step 5: Add the remaining raw materials to the material in step 4, stir at a speed of 1000 r / min for 8 minutes to obtain a long-lasting antifreeze coolant with ultra-low conductivity.

[0074] Table 1 Comparative Example Comparative Example 1 An ultra-low conductivity long-term antifreeze coolant, which is different from Example 1 in that the modifier is omitted.

[0075] Comparative Example 2 A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity is different from that of Example 1 in that the raw materials for preparing the modifier are different, and coconut shells are replaced by sugarcane.

[0076] The specific steps include: Step 1a: Wash the sugar cane with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the sugar cane into particles with a size of 0.1-0.3 mm to obtain sugar cane powder.

[0077] Step 1b: Mix sugarcane powder and deionized water in a ratio of 1:5.

[0078] Then, the mixture was treated with microwaves at 350 W for 15 min to obtain a microwave-treated product.

[0079] Step 1c: Heat the microwave-treated product at 230° C. for 3 h to obtain a heated reaction product.

[0080] Step 1d: Filter the heated reactants, and dry the solid portion using hot air to a constant weight to obtain a product to be treated.

[0081] Step 1e: Mix the object to be treated with nano-alumina (nano-alumina particle size is 20nm) at a mass ratio of 1:0.5 and place in a tube furnace. Heat to 700°C at a heating rate of 10°C / min, react for 5h in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it under hot air at 60°C to constant weight to obtain a modifier.

[0082] Comparative Example 3 A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity is different from that of Example 1 in that microwave treatment is omitted.

[0083] The specific steps include: Step 1a: Wash the coconut shell with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the coconut shell into particles with a diameter of 0.1-0.3 mm to obtain coconut shell powder.

[0084] Step 1b: Mix coconut shell powder with deionized water in a ratio of 1:5.

[0085] Step 1c: heating the material of step 1b at 230° C. for 3 h to obtain a heated reactant.

[0086] Step 1d: Filter the heated reactants, and dry the solid portion using hot air to a constant weight to obtain a product to be treated.

[0087] Step 1e: Mix the object to be treated with nano-alumina (nano-alumina particle size is 20nm) at a mass ratio of 1:0.5 and place in a tube furnace. Heat to 700°C at a heating rate of 10°C / min, react for 5h in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it under hot air at 60°C to constant weight to obtain a modifier.

[0088] Comparative Example 4 A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity is different from that of Example 1 in that the heating treatment is omitted.

[0089] The specific steps include: Step 1a: Wash the coconut shell with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the coconut shell into particles with a diameter of 0.1-0.3 mm to obtain coconut shell powder.

[0090] Step 1b: Mix coconut shell powder with deionized water in a ratio of 1:5.

[0091] Then, the mixture was treated with microwaves at 350 W for 15 min to obtain a microwave-treated product.

[0092] Step 1c: Filter the microwave-treated product, and use hot air to dry the solid portion to a constant weight to obtain a product to be treated.

[0093] Step 1d: Mix the object to be treated with nano-alumina (nano-alumina particle size is 20nm) at a mass ratio of 1:0.5 and place in a tube furnace. Heat to 700°C at a heating rate of 10°C / min, react for 5h in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it to constant weight under hot air at 60°C to obtain a modifier.

[0094] Comparative Example 5 A method for preparing a long-lasting antifreeze coolant with ultra-low conductivity is different from that of Example 1 in that the calcination temperature of step 1e is changed.

[0095] The specific steps include: Step 1a: Wash the coconut shell with deionized water, dry it with hot air to constant weight, and then use a crusher to chop the coconut shell into particles with a diameter of 0.1-0.3 mm to obtain coconut shell powder.

[0096] Step 1b: Mix coconut shell powder with deionized water in a ratio of 1:5.

[0097] Then, the mixture was treated with microwaves at 350 W for 15 min to obtain a microwave-treated product.

[0098] Step 1c: Heat the microwave-treated product at 230° C. for 3 h to obtain a heated reaction product.

[0099] Step 1d: Filter the heated reactants, and dry the solid portion using hot air to a constant weight to obtain a product to be treated.

[0100] Step 1e: Mix the object to be treated with nano-alumina (nano-alumina particle size is 20nm) at a mass ratio of 1:0.5 and place in a tube furnace. Heat to 500°C at a heating rate of 10°C / min, react for 5h in a N2 atmosphere, wait for the tube furnace to cool naturally to room temperature, wash the obtained product with ethanol several times to remove impurities, and then dry it under hot air at 60°C to constant weight to obtain a modifier.

[0101] Performance testing 1. Thermal conductivity: The ultra-low conductivity long-acting antifreeze coolants of Examples 1-3 and Comparative Examples 1-5 were tested at 20° C. using a thermal conductivity tester, and the thermal conductivity was recorded in Table 2.

[0102] 2. Conductivity: The ultra-low conductivity long-acting antifreeze coolants of Examples 1-3 and Comparative Examples 1-5 were tested with reference to GB / T 29743.2 "Electric Vehicle Coolant", and the conductivity was recorded in Table 2.

[0103] Other properties of Examples 1-3 and Comparative Example 1 are detailed in Table 3, and the tests were performed with reference to GB / T 29743.2 "Electric Vehicle Coolant".

[0104] Table 2 Table 3 Comparative Example 1 is based on Example 1, but the modifier is omitted. According to the test data in Table 2, the coolant in Example 1 has a higher thermal conductivity and a lower electrical conductivity than that in Comparative Example 1, which indicates that the coolant in Example 1 can achieve a faster cooling effect and has more significant insulation.

[0105] Combined with the test data in Table 3, it can be seen that the freezing point of the coolant in Examples 1-3 is lower than that in Example 1, and the boiling point is higher than that in Comparative Example 1. The coolants in Examples 1-3 show lower corrosivity than Comparative Example 1 in corrosion tests of various materials. This shows that the performance of Example 1 is better than that of Comparative Example 1 in all aspects. This shows that the coolant provided in this application is indeed more suitable for use in new energy vehicles and has excellent performance.

[0106] Comparative Example 2 is based on Example 1, with the coconut shell replaced by sugarcane. Comparative Examples 3-5 are based on Example 1, with the preparation conditions of the modifier changed. According to the test data in Table 2, the thermal conductivity of the coolant in Comparative Examples 2-5 is significantly lower than that in Example 1, and the electrical conductivity is significantly increased. This shows that the specific raw materials and specific preparation conditions of the modifier are crucial to the formation of the modifier structure. Randomly changing the preparation raw materials, microwave conditions, heating conditions or calcination temperature of the modifier will have a great impact on the load structure of the modifier, so that the coolant cannot show excellent high insulation and high thermal conductivity effects.

[0107] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.

Claims

1. A long-lasting antifreeze coolant with ultra-low conductivity, characterized in that: According to mass percentage, it includes the following components: 0.1-0.2% copper corrosion inhibitor, 0.15-0.22% aluminum corrosion inhibitor, 0.18-0.25% pH value regulator, 0.01-0.05% defoamer, ethylene glycol, 35-45% deionized water, and 0.01-0.05% modifier; The modifier is prepared by carbonizing coconut shell and loading nano-alumina.

2. The ultra-low conductivity long-lasting antifreeze coolant according to claim 1, characterized in that: The copper corrosion inhibitor comprises a mixture of one or more of benzotriazole, tolutriazole and sodium mercaptobenzothiazole.

3. The ultra-low conductivity long-lasting antifreeze coolant according to claim 1, characterized in that: The aluminum corrosion inhibitor includes a mixture of one or more of sodium silicate and phenyl silicate.

4. The ultra-low conductivity long-lasting antifreeze coolant according to claim 1, characterized in that: The particle size of the nano-alumina is 10-30nm.

5. A method for preparing the ultra-low conductivity long-acting antifreeze coolant according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: preparing a modifier, comprising the following steps: Step 1a: chopping coconut shells to obtain coconut shell powder; Step 1b: mixing coconut shell powder with deionized water, and subjecting the mixture to microwave treatment at 300-400 W for 10-20 min to obtain a microwave-treated product; Step 1c: heating the microwave-treated product at 200-250° C. for 2-4 h to obtain a heated reaction product; Step 1d: filtering, drying and heating the reactants to obtain a product to be treated; Step 1e: uniformly mixing the object to be treated with nano-alumina, and then calcining at 650-750° C. for 4-6 hours to obtain a modifier; The mass ratio of the object to be treated to the nano-alumina is 1:(0.3-0.6), based on the mass of the object to be treated; Step 2: Mix ethylene glycol and deionized water until uniform; Step 3: Add the pH adjuster to the material in step 2 and mix well; Step 4: Cool the material in step 3 to below 50°C, add copper corrosion inhibitor and aluminum corrosion inhibitor, and stir until completely dissolved; Step 5: Add the remaining raw materials to the materials in step 4 and mix until uniform to obtain a long-lasting antifreeze coolant with ultra-low conductivity.

6. The method for preparing the ultra-low conductivity long-acting antifreeze coolant according to claim 5, characterized in that: In the step 1b, the mass ratio of coconut shell powder to deionized water is 1:(3-6), based on the mass of coconut shell powder.

7. The method for preparing the ultra-low conductivity long-acting antifreeze coolant according to claim 5, characterized in that: The particle size of the coconut shell powder is 0.1-0.3 mm.

8. The method for preparing the ultra-low conductivity long-acting antifreeze coolant according to claim 5, characterized in that: After the remaining raw materials are added in step 5, stirring is performed at a rotation speed of 800-1000 r / min.

Citation Information

Cited By

  • Nano aluminum oxide-n-amyl alcohol synergistic heat conduction type low-conductivity cooling liquid

    CN121780141A